On a new distinguishing feature of the species Trechus obtusus and Trechus quadristriatus (Coleoptera: Carabidae). - Hirschfelder, Angelika; Zucchi, Herbert (Contributions to Entomology = Beiträge zur Entomologie, 1993)
The carabid species Trechus obtusus Erichson 1837 and Trechus quadristriatus (Schrank 1781) are, in their outward appearance, very similar to each other. A new distinguishing feature is submitted.